A depiction of Maphalla’s message in his poems: The case of Ke ikopela tokoloho and Mahlo a ka tutuboloha - Ntsoaki T. Mokala; Soyiso G. Khethoa (Literator, 2023)
In this article, we argue that KPD Maphalla’s poems were very influential in portraying protest to different forms of social oppression and exclusion in South Africa and Africa at large. Therefore, as a writer who was subjected to racial segregation during the apartheid regime, he positioned himself as a social poet concerned about the sociopolitical situation of Africans in Africa. The article illustrates how Maphalla’s use of tone and attitude towards racial discrimination has shown his ability to choose style in articulating a clear sociopolitical protest. This strategy has helped to make his readers aware of the social anomalies of his time, while condemning moral degeneration of that era. Therefore, this article provides an analysis of two poems from his book entitled Kgapha tsa ka: Mahlo a ka tutuboloha (My eyes open) and Ke ikopela tokoholo (I am asking for freedom), to understand the influence of the selected poems that are constructed in the form of protest. A historical-biographical criticism framework was employed in this case study to unravel the sociopolitical influence of his work towards the fight for freedom in South Africa. It is a qualitative explorative study, which uses purposive sampling to show how he portrays the theme of protest in his poems. Content analysis was used to analyse data guided by interpretivist paradigm.